2014
DOI: 10.3310/hta18640
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risk of self-harm in an adult offender population: an incidence cohort study

Abstract: BackgroundSelf-harm is common among prisoners, particularly female prisoners. In 2007, concerned about the rising incidence, the prison service introduced a care-planning system called Assessment, Care in Custody, and Teamwork (ACCT). To date, it does not incorporate a standardised diagnostic test to estimate the risk of future self-harm.ObjectiveTo identify potential screening instruments, or items from those instruments, to predict the risk of self-harm among prisoners.ParticipantsPrisoners who had been assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 83 publications
0
17
0
2
Order By: Relevance
“…This study sought to identify independent predictors of self-directed aggression (suicidal behavior and/or self-mutilation), in a large sample of incarcerated Italian men. Both suicidal behavior and self-mutilation are more common in prisoners than the general population and these behaviors are frequently comorbid (Carli et al 2011a;Fazel & Danesh 2002;Horton et al 2014;Jenkins et al 2005;Stanley et al 2001). Indeed, one third of our sample with self-directed aggression had a lifetime history of both suicidal behavior and self-mutilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study sought to identify independent predictors of self-directed aggression (suicidal behavior and/or self-mutilation), in a large sample of incarcerated Italian men. Both suicidal behavior and self-mutilation are more common in prisoners than the general population and these behaviors are frequently comorbid (Carli et al 2011a;Fazel & Danesh 2002;Horton et al 2014;Jenkins et al 2005;Stanley et al 2001). Indeed, one third of our sample with self-directed aggression had a lifetime history of both suicidal behavior and self-mutilation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that 77% of US prisoners who attempted suicide had psychiatric disorders compared with 15% in the general prison population (Goss et al , 2002). A few studies have shown that self-mutilation is also common in prisoners (Carli et al , 2011a, Horton et al , 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Nowhere are the problems more apparent than in the criminal justice system where Aboriginal and Torres Strait Islander Australians are grossly overrepresented, accounting for about 30% of adult prisoners in Australia although they make up only 2% of the Australian population. 2,3 Many Aboriginal and Torres Strait Islander Australians cycle between prison and the community with their needs unmet. The high rates of short-term repeated incarceration have a multitude of negative health effects for Aboriginal families, communities, and wider society.…”
Section: Making Visible the Invisible: Aboriginal Forensic Mental Healthmentioning
confidence: 99%
“…Prevention of suicide is a key task for correctional institutions but identifying individuals most at risk of suicide in prison is not simple, with the limitations of risk assessment for accurately identifying individuals most at risk of suicide having been acknowledged. 2,3 This problem has led researchers to investigate the role of institutional, systemic, and environmental factors that might influence prisoner suicide, in the hope of identifying modifiable targets for intervention.…”
mentioning
confidence: 99%
“…There are conflicting data about the possibility of a predictive score for self-harm / suicide. Thus, while authors from the UK use a psychometric instrument (SCOPE) designed to distinguish between those at risk and those with no risk of self-harm [7], other authors refute this possibility [6,8].…”
Section: Discussionmentioning
confidence: 99%